A phase II multicenter trial assessing the efficacy and safety of first-line S-1 + ramucirumab in elderly patients with advanced/recurrent gastric cancer: KSCC1701. (May 2022) - Kobayshi, Kazuma; Suyama, Koichi; Katsuya, Hiroo; Izawa, Naoki; Uenosono, Yoshikazu; Hu, Qingjiang; Kusumoto, Tetsuya; Otsu, Hajime; Orita, Hiroyuki; Kawanaka, Hirofumi; Shibao, Kazunori; Koga, Satoshi; et al.
Abstract: Background: The mainstream first-line chemotherapy for advanced/recurrent gastric cancer (ARGC) is combination therapy including platinum-based agents. With the progressive aging of the society, the incidence of gastric cancer in elderly patients is increasing. However, elderly patients cannot tolerate these agents because of renal dysfunction or low quality of life. The KSCC1701 study explored the efficacy and safety of S-1 + ramucirumab in elderly patients with ARGC. Patients and methods: Chemotherapy-naive patients aged ≥70 years with ARGC were eligible. Patients received S-1 (40–60 mg twice daily for 4 weeks in 6-week cycles) and ramucirumab (8 mg/kg every 2 weeks) until disease progression. The primary end-point was the 1-year overall survival (OS) rate. The anticipated lower threshold of 1-year survival was set at 40% in light of previous S-1–based regimens. The secondary end-points included progression-free survival (PFS), OS, the overall response rate (ORR) and safety. Results: Between September 2017 and November 2019, 48 patients (34 men and 14 women) were enrolled in this study. The median patient age was 77.5 years, and all patients had a performance status of 0 (n = 20) or 1 (n = 28). The 1-year OS rate was 65.2%, which met the primary end-point. The median survival time and median PFS were 16.4 and 5.8 months, respectively. The ORR was 41.9%. The most frequent grade 3/4 (≥15%) adverse events were neutropenia, anorexia and anaemia. Conclusion: Considering these findings, S-1 + ramucirumab appears to be an excellent treatment option for elderly patients with ARGC. (250 words). This trial has been registered with the Japan Registry of Clinical Trials Registry under the number jRCTs071180066. Highlights: Elderly ARGC patients with good performance status were enrolled. Explored the efficacy and safety of S-1 + ramucirumab, achieved good OS. PFS and ORR were also sufficient results. Frequent grade 3/4 (≥15%) adverse events were neutropenia, anorexia and anaemia.